Sintesa Surfaktan Ramah Lingkungan Metil Ester Sulfonat Dari Palm Oil Methyl Ester Menggunakan Natrium Metabisulfit Dan Katalis Aluminium Oksida - Suhendri Suhendri; Nirwana Nirwana; Irdoni Irdoni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Surfactants is surface active agents that can reduce interfacial tension between the two materials in the form of liquid-liquid, liquid-solid, or liquid-gas. Methyl Ester Sulfonate (MES) is one type of anionic surfactant which has advantages in terms of detergency, resistant to hardness, renewable and eco-friendly. Methyl Ester Sulfonate produced by the process of sulfonation between Palm Oil Methyl Ester (POME) and sulfonation agent sodium metabisulphite (Na2S2O5) with a catalyst of aluminum oxide (Al2O3). This study aims to make a methyl ester sulfonate by using variations mole ratio and reaction time. Sulfonation process was performed using palm oil methyl ester and sulfonation agent sodium metabisulfite Compounds with variations mole ratio of 1:0.5; 1:1; 1:1.5 and variation reaction time 3; 4.5 and 6 hours. The catalyst was aluminum oxide 1% w/w POME. Sulfonation process was in 100 °C with 450 stirring speed. After a reaction time had been reached, the product was washed by water and allowed to stand for 24 hours. The result showed the best products on the use the mole ratio of 1:1.5 with a reaction time of 4.5 hours. analysis of physical-chemical properties of products shows that the MES pH value of 2.80, the density of 0.8736 g/mol, 2.1244 cp viscosity, surface tension decrease of 25.10 dyne/cm of 71.40 dyne/cm to 46.30 dyne/cm, decrease interfacial tension of water - xylene of 6.80 dyne/cm of 35.80 dyne/cm 29.00 dyne/cm with a value of 88.33% emulsion stability.Keyword: Anionic Surfactants, Methyl Ester Sulfonate